Historical Perspective of Trade Relation Between the Nyishi and Tibetan - Yab Rajiv Camder; Philip Mody; Tok Kumar (Dera Natung Government College Research Journal)
Trade is one of the main sources of development of any region. It is an essential part of every human civilization. Times out of mind, the Nyishi tribe is known to have been maintaining trade relation with Tibetan counterpart. It is believed that Nincgh Yayi were the first people who had started Nyeme Pudung Rongnaam which means ‘marching toward Tibet especially for trade’. During those Nyeme Pudung, Nyishi people faced lots of hurdles during their journey to Tibet (China) to carry out trading activities. Fascinatingly, those hurdles became folk tales. Subsequently, in famous folk tales like Aachi Aachiya Rupche (Dimum Ren), Aach Yashi, Hadu Daachar etc, of Nyishi community came into existence. Further, the Nyishi and Tibetans had barter trading in which goods were exchanged for other goods. In the course of trading, Nyishi people had exported skins, testis, teeth, claw of many wild animals, Pud Ejeh etc. Likewise, Nyishis had been importing Mapu Aalu (salt), Ruar Aryu (sword), Sangte & Sangter Tasang (beads), Maji (kinds of bell), Talu (brass plate) etc from Tibetans. With this background, the paper makes an attempt to provide a historical account of economy of the Nyishi community. Also, it shall provide a historical perspective of trade relation between Nyishi and Tibetans.